IDENTIFIKASI KEPUASAN KONSUMEN TERHADAP ATRIBUT PRODUK PEMBANGKIT LISTRIK ENERGI ALTERNATIF DENGAN MENGGUNAKAN KANO’S MODEL DI LANGKAT - Ginting, Rosnani; Siregar, Ikhsan (Jurnal Sistem Teknik Industri, 2018)
Alternative energy is a term that refers to all usable energy that aims to replace conventional fuels without any unintended consequences. In the context of this research, alternative energy is meant as renewable energy. Renewable energy is energy generated from natural sources, such as sunlight, wind, rain, tidal currents, and geothermal, which are renewable or can reappear naturally after its utilization. Many methods, procedures and techniques are adopted by the customer satisfaction as enhanced by the design of An Alternative Energy Utilization. This study seeks an assessment of user satisfaction, which in this case is the community, to combine Quality Function Deployment and Kano's model as design techniques in product design and development by focusing on capturing and translating consumer desires into a product design. The calculation results show the most important characteristic to be immediately corrected is Technology sophistication and Production Cost with the highest cost estimate, the degree of importanceand difficulty level. From the planning matrix obtained the product attribute that is Generation Price and Durability become the priority of improvement because it has the biggest weight.